Review of Wayne D. Bowman and Ana Lucía Frega, eds. 2012. The Oxford Handbook of Philosophy in Music Education. London and New York: Oxford University Press. - Abramo, Joseph (Current Musicology, 2012)
All musicians, regardless of their chosen area of study, take on the role of an educator at some point in their career. As Luis Alfonso Estrada Rodgriquez writes, “[m]any musicians devote time in their lives in one way or another to teaching. This is, however, an activity that in many cases was not taken into account in their studies” (240). In particular, music theorists and musicologists often serve as instructors in higher education and, therefore, devote many hours to the pedagogy of music. The Oxford Handbook of Philosophy in Music Education, edited by Wayne Bowman and Ana Lucía Frega—a collection of writings from leading, contemporary music education philosophers—provides a useful resource for those academics of music that find themselves in this common position. In this review, first I briefly provide the historical progression of music education philosophy over the last forty years in order to situate the ideas and themes for readers outside the field of music education. Second, I highlight some important themes within the book, focusing on connections among the chapters rather than addressing them separately. Third, I suggest how academics outside of the field of education may apply it to higher education. Finally, I remark on the connection between theory and practice in this text and music education scholarship and look to the future.